The Influence of Product Design Practices on New Service Development: Analysis of Selected Manufacturing Firms - Sayar, Deniz; Er, Özlem (Wiley, 2017)
This article investigates the influence of product design practices on new service development processes of manufacturers that are moving toward service provision using a multiple case study conducted with four companies. Technological developments, a competitive business environment, and diverse customer demands have forced manufacturing firms to pursue growth strategies through new service development. On the other hand, studies on design, particularly the interplay between product design and new service development processes, in this shift are scant. This is significant because a manufacturer's transition from only selling products toward delivering services requires the simultaneous management of practices that reflect their histories of product design and processes that comprise service design and development. As a result of the analysis, three themes emerged regarding the influence of product design practices on new service development within the context of manufacturing: (1) accumulation of product design expertise, (2) increased customer loyalty through high‐quality products, and (3) design problems as tools for fostering innovation culture. Each theme is thoroughly discussed with examples from the case study companies. Consequently, this article highlights the interplay between product and service design processes and provides insights on how established product design practices would assist a manufacturer in service provision.